Open Source Mesh Generation and CFD Simulations for Francis Turbine - Kapoor, Himanshu (My University, 2014)
Hydro power can be recognised as a relatively mature technology of all renewable energies. Efficiency around 90 % are commonly observed in Francis turbines. Since hydro power is relatively cheaper among other power sources, it is used as base power in energy systems. Additionally hydro-power plants are often operated at offdesign conditions, which may lead to cavitation. Accordingly design improvements for improving the efficiency of the turbine at off design conditions are of great interest to designers. Computational fluid dynamics is used often for this analysis for predicting fluid flows as per modified design. In the field of Computational Fluid Dynamics, open source software have developed a significant role in past few years due to economical reasons and providing user access to the source code. In many published works it has been successfully shown that the OpenFOAM solver produces comparable results to commercial codes. Most of the published work on OpenFOAM uses a mesh generated by a commercial software, most commonly on ICEM. As a step further in this thesis work, mesh has been generated on open source software for a typical Francis turbine. The geometry used for this work has been used from experimental rig for Francis turbine at Applied Mechanics Department. Further possibilities of parametrisation in terms of geometry and mesh distribution have been explored. For diffuser complete parametrisation of geometry and mesh is achieved, for guide vane and Runner a structured mesh of acceptable quality has been made. To validate the mesh and mesh generation procedure simulations were carried out various operating conditions to analyse the flow. Two equation RANS models, standard k-e and it's variant RNG k-e model have been used for turbulence modelling. The efficiency of turbine did not vary much with choice of turbulence models. Overall it can be concluded that Open Source Software for mesh generation and CFD simulations can be successfully used for R&D in academia and industry.
Keywords: Hållbar utveckling; Energi; Strömningsmekanik; Innovation och entreprenörskap (nyttiggörande); Sustainable Development; Energy; Fluid mechanics; Innovation & Entrepreneurship